3
$\begingroup$

Where do I start to solve a equation for x like the one below?

$$\sqrt{7x-4}-\sqrt{7x-5}=\sqrt{4x-1}-\sqrt{4x-2}$$

After squaring it, it's too complicated; but there's nothing to factor or to expand?

Ideas?

$\endgroup$
  • $\begingroup$ Did you try rational zero theorem on your polynomial. There is a rational zero. $\endgroup$ – imranfat May 23 '13 at 17:04
10
$\begingroup$

Divide $$(7x-4)-(7x-5)=(4x-1)-(4x-2)\ \ \ \ \ (1)$$ by the original equation, which is $$\sqrt{7x-4}-\sqrt{7x-5}=\sqrt{4x-1}-\sqrt{4x-2}\ \ \ \ \ (2)$$ You should get:$$\sqrt{7x-4}+\sqrt{7x-5}=\sqrt{4x-1}+\sqrt{4x-2}\ \ \ \ \ (3)$$Now add (2) and (3), you get: \begin{align} 2\sqrt{7x-4}&=2\sqrt{4x-1} \\ \\ 7x-4&=4x-1 \\ \\ x&=1 \end{align}

| cite | improve this answer | |
$\endgroup$
5
$\begingroup$

Note that

$$ \sqrt{7x-4} - \sqrt{7x-5} = \frac{(7x-4)-(7x-5)}{\sqrt{7x-4} + \sqrt{7x-5}} = \frac{1}{\sqrt{7x-4} + \sqrt{7x-5}} $$

and likewise

$$ \sqrt{4x-1} - \sqrt{4x-2} = \frac{1}{\sqrt{4x-1} + \sqrt{4x-2}}. $$

Plugging these to our equation, we obtain

$$ \sqrt{7x-4} + \sqrt{7x-5} = \sqrt{4x-1} + \sqrt{4x-2}. $$

Thus we have

$$ \sqrt{7x-4} = \sqrt{4x-1} \quad \text{and} \quad \sqrt{7x-5} = \sqrt{4x-2}, $$

yielding $x = 1$.

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

From $$\sqrt{7x-4}-\sqrt{7x-5}=\sqrt{4x-1}-\sqrt{4x-2}$$ multiply both sides by $$(\sqrt{7x-4}+\sqrt{7x-5})\times(\sqrt{4x-1}+\sqrt{4x-2})$$ obtaining $$\sqrt{4x-1}+\sqrt{4x-2} =\sqrt{7x-4}+\sqrt{7x-5}$$ so that $$2\sqrt{4x-1}=2\sqrt{7x-4}$$

And after dividing by $2$ and squaring, obtain $x=1$.

Note: this underlies he other answers so far given, but this approach is a form of "multiplying by the conjugate" which comes in handy in a variety of situations.

| cite | improve this answer | |
$\endgroup$
2
$\begingroup$

$$\sqrt{7x-4}-\sqrt{7x-5}=\sqrt{4x-1}-\sqrt{4x-2}$$

$$\implies \sqrt{7x-4}+\sqrt{4x-2}=\sqrt{4x-1}+\sqrt{7x-5} $$

Squaring we get, $$7x-4+4x-2+2\sqrt{(7x-4)(4x-2)}=4x-1+7x-5+2\sqrt{(4x-1)(7x-5)}$$

$$\implies \sqrt{(7x-4)(4x-2)}= \sqrt{(4x-1)(7x-5)}$$

$$\text{Squaring we get, } (7x-4)(4x-2)=(4x-1)(7x-5)$$

$$\text{ On simplification we get, 8-(16+14)x=5-x(20+7)} $$

$$\implies x=1,\text{ which evidently satisfies the given equation. }$$

Generalization:

If $$\sqrt{ax+b}-\sqrt{ax+c}=\sqrt{dx+e}-\sqrt{dx+f} \text{ where }b-c=e-f$$

$$\implies \sqrt{ax+b}+\sqrt{dx+f}=\sqrt{dx+e}+\sqrt{ax+c} $$

Squaring we get, $$ax+b+dx+f+2\sqrt{(ax+b)(dx+f)}=dx+e+ax+c+2\sqrt{(dx+e)(ax+c)} $$

$$\implies \sqrt{(ax+b)(dx+f)}=\sqrt{(dx+e)(ax+c)}\text{ as } b-c=e-f\iff b+f=c+e $$

$$\text{Squaring we get, } (ax+b)(dx+f)=(dx+e)(ax+c)$$

$$\implies x(bd+af-cd-ae)=ec-bf $$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

Hint: below let $\, a,b,c,d\, =\, \sqrt{7x\!-\!4},\ \sqrt{7x\!-\!5},\ \sqrt{4x\!-\!1},\ \sqrt{4x\!-\!2}$

$$\begin{eqnarray} & a^2-b^2 &=\,& c^2-d^2 \ne 0 \\ & a-b &=\,& c-d \\ \Rightarrow & a+b &=\,& c+d\quad \text{via quotient of above two} \\ \Rightarrow & \qquad 2a &=\,& 2c\qquad\ \text{via sum of above two} \\ \Rightarrow &\qquad a &=\,& c\,\ \Rightarrow\ b=d \\ \Rightarrow &\qquad a^2 &=\,& c^2 \Rightarrow\ b^2\!=d^2 \end{eqnarray}$$

| cite | improve this answer | |
$\endgroup$
1
$\begingroup$

1.Rewrite the equasion as: $$ \sqrt {7x-4} + \sqrt {4x-2} = \sqrt {7x-5} + \sqrt {4x -1} $$

2.Function $\sqrt {7x-4} + \sqrt {4x -2} $ is strictly increasing (i.e always increasing).

3.Function $\sqrt {7x-5} + \sqrt {4x -1} $ is strictly increasing (i.e always increasing) too.

Plotting a graph will show that there will be only one interception. With the help of this graph or by knowlegable guessing one can find that $x=1$.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.